2004
DOI: 10.1002/cncr.20746
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic procedures after a positive spiral computed tomography lung carcinoma screen

Abstract: BACKGROUNDLow‐radiation dose spiral computed tomography (LDCT) currently is being evaluated as a screening modality for lung carcinoma in a randomized trial. Although several diagnostic algorithms for the workup of positive LDCT screens have been proposed, to the authors' knowledge there is no widely accepted standard to date and there are few nationwide data concerning how such diagnostic workups are actually being performed outside a research protocol setting.METHODSThe Lung Screening Study (LSS) was a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Fifteen percent of the subjects had at least one abnormality in their baseline spiral CT, 10.1% of the spiral CT patients have had at least one extra diagnostic procedure, 4.2% an invasive procedure, and 18.7% of the thoracotomies in the spiral CT arm were done for a benign pulmonary lesion. However, on the whole our data compare favourably with those from most other study groups [10,13,14,30,37,38]. For instance, in the Mayo Clinic study, the reported percentage of thoracotomies carried out for benign pulmonary lesions was 18.1% [38].…”
Section: Discussionsupporting
confidence: 81%
“…Fifteen percent of the subjects had at least one abnormality in their baseline spiral CT, 10.1% of the spiral CT patients have had at least one extra diagnostic procedure, 4.2% an invasive procedure, and 18.7% of the thoracotomies in the spiral CT arm were done for a benign pulmonary lesion. However, on the whole our data compare favourably with those from most other study groups [10,13,14,30,37,38]. For instance, in the Mayo Clinic study, the reported percentage of thoracotomies carried out for benign pulmonary lesions was 18.1% [38].…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, our results show a high frequency of thoracotomy or VATS without cancer and an apparent community bias toward aggressive intervention with biopsy for persons with indeterminate lung nodule. Observing 12% of 522 subjects having a biopsy within 1 year of a positive screening CT, Pinsky and colleagues also describe an apparent community bias toward biopsy (17). These results argue for strict adherence to diagnostic guidelines, in combination with informed decision making, when managing persons with nodules detected on screening CT.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, comparing outcomes observed in three large studies of CT screening to predictions from two validated risk models, the second analysis concluded that CT screening increases lung cancer diagnosis and lung cancer resection without decreasing advanced lung cancer or lung cancer death (14). In addition to over-diagnosis (screen-detection and treatment of clinically insignificant or indolent lung cancer), CT screening frequently detects benign abnormalities (generally, nonmalignant noncalcified lung nodules) that can lead to anxiety, costs, and unnecessary procedures (16,17).…”
mentioning
confidence: 99%
“…Definitive conclusions about CT screening and lung cancer mortality await results from randomized trials in the US [8] and Europe [10][13]. CT can detect small, early-stage lung tumors, but distinguishing rare cancers from common benign conditions is difficult and has led to unnecessary procedures, radiation exposure, anxiety, and cost [6], [14][16]. We (J.M.S., J.L.W., and colleagues) recently reported such conclusions for the Pittsburgh Lung Screening Study (PLuSS), the largest single-institution CT screening study reported to date [5].…”
Section: Introductionmentioning
confidence: 99%